Comparative Evaluation of Biomechanical Performance of Titanium and Stainless Steel Mini Implants at Different Angulations in Maxilla: A Finite Element Analysis. Issue 3 (July 2019) - Sabley, Kshitij Hemant; Shenoy, Usha; Banerjee, Sujoy; Akhare, Pankaj; Hazarey, Ananya; Karia, Himija
Abstract: Objective: To assess and compare the tensions and deformations (stresses and strains) generated after application of two types of forces (traction and torsion) in miniscrews of two different materials (titanium and stainless steel) placed at five different angulations. Materials and Methods: Three-dimensional models of the posterior maxillary area and the mini-implants were constructed using computer-aided design software program (CATIA P3 V5-6 R2015 B26 / 2016; Dassault Systèmes). Titanium and stainless steel materials were used for miniscrews. The area constructed was in between the maxillary second premolar and first molar. The models with mini-implants were inserted at five different angulations (30°, 45°, 60°, 75° and 90°). Torsional and tractional forces were applied on these implants, and the models were solved using ANSYS 10.0. Stress generated in implant and in the cortical and cancellous bones was evaluated and compared at all the five angulations. Results: Stress generated in stainless steel mini-implant during torsional and linear force application was less when compared with titanium mini-implant. Also, stress generated in implants of both materials increased as the angle increased from 30° to 90°. Difference in stress generated by stainless steel implant in the cortical bone for both linear and torsional forces was less when compared with titanium implant, whereas for cancellous bone, the difference was insignificant at all the angles. Conclusion: Irrespective of angles, difference in stress generated in stainless steel implants and titanium implants for both the forces was not significant, and hence, stainless steel implants can be used effectively in a clinical setting.